A free surface corrected lumped parameter model for near-surface horizontal maneuvers of underwater vehicles in waves. (15th June 2023) - Lambert, William; Miller, Lakshmi; Brizzolara, Stefano; Woolsey, Craig
Abstract: We provide theory and results obtained from the application of a 6-degree of freedom lumped parameter maneuvering model (LPMM) able to predict the maneuvering motions of underwater vehicles navigating at shallow depth below free surface waves. The parameters of the maneuvering model are identified using a combination of steady and unsteady captive maneuvers, simulated with high fidelity computational fluid dynamic (CFD) methods. This work focuses on correcting the LPMM, which is accurate for deep water motions, to account for free surface effects. A frequency domain strip theory method is used to account for changes in the added mass due to free surface proximity, to calculate memory forces, and to estimate wave excitation forces while a 3D time domain boundary element method is used to predict steady-state wave making forces. The result is a combined maneuvering and seakeeping model for underwater vehicles operating at shallow depths below the free surface. Near-surface horizontal zig-zag motion predictions in both calm water and under waves reveal the importance of including the free surface as vehicle trajectories at shallow depths differ substantially from those at deeper submergences for identical maneuvering inputs. Highlights: Surface effects are important in the calculation of added mass and damping. A deep water maneuvering model for AUVS is updated for surface proximity effects. Wave excitation forces and memory effects are estimated using strip theory methods. Near-surface horizontal zig-zag motions at varying depths are shown for a VT690 AUV.